Penanaman Mangrove dan Cemara Laut Sebagai Upaya Pelestarian Lingkungan di Pantai Wonogoro - Pudjiastuti, Widanarni; Maria, Evi; Rahmawati, Rina; Hariadi, Sugeng; Aryani, Dwi Nita; Bunyamin, Bunyamin; Munfaqiroh, Siti (STIE Malangkucecwara, 2024)
Mangrove and sea cypress planting activities at Wonogoro Beach, Malang, East Java, are environmental conservation activities carried out by the STIE Malangkucecwara Community Service Team and international students from the International Community Service (ICS). This activity aims to overcome coastal erosion problems, preserve coastal ecosystems, improve air quality, enhance tourism potential and increase international cooperation. The implementation method includes socialising with the surrounding community and planting mangrove and sea cypress seedlings in the coastal area. This activity has been successfully implemented and positively received by the Wonogoro Beach community. Although there are several obstacles, the Community Service Team has tried to overcome them. Recommendations include continuous socialisation, monitoring and evaluation of plant growth, and collaboration with related parties to increase the effectiveness of the activities.